2019
DOI: 10.1596/978-1-4648-1404-4
|View full text |Cite
|
Sign up to set email alerts
|

Back to School: Pathways for Reengagement of Out-of-School Youth in Education

Abstract: Books in this series are published to communicate the results of Bank research, analysis, and operational experience with the least possible delay. The extent of language editing varies from book to book. This work is a product of the staff of The World Bank with external contributions. The findings, interpretations, and conclusions expressed in this work do not necessarily reflect the views of The World Bank, its Board of Executive Directors, or the governments they represent. The World Bank does not guarante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 121 publications
(168 reference statements)
0
23
0
Order By: Relevance
“…To facilitate this scope, isolated strategies like one-to-one adult-youth mentoring [18], life skill development through sports and physical activity [19], and academic or work-based learning and training [20] have so far been adopted across Europe and beyond. However, being limited in scope, reports have suggested that such singular efforts may be insu cient to meet the complex needs of young people in more vulnerable 'NEET' situations, while initiatives that combine different resources may resonate better with their varied interests, talents, and abilities [21,22].…”
Section: Scope and Aim Of The Projectmentioning
confidence: 99%
“…To facilitate this scope, isolated strategies like one-to-one adult-youth mentoring [18], life skill development through sports and physical activity [19], and academic or work-based learning and training [20] have so far been adopted across Europe and beyond. However, being limited in scope, reports have suggested that such singular efforts may be insu cient to meet the complex needs of young people in more vulnerable 'NEET' situations, while initiatives that combine different resources may resonate better with their varied interests, talents, and abilities [21,22].…”
Section: Scope and Aim Of The Projectmentioning
confidence: 99%
“…Particularly, a thoughtfully designed multi-component programme that combines one-to-one mentoring, positive youth development, and sport and physical activity programmes, may be useful (cf. Rajasekaran & Reyes, 2019). Despite this recommendation, to my knowledge, no programme drawing on the full range of available modalities has been utilised or evaluated with disengaged young people.…”
Section: Tackle Journey Cards……………………………………………………………249mentioning
confidence: 99%
“…There is general consensus that disengaged young people subsume a heterogeneous mix of individuals who face many complex, fluctuating, and nonlinear transitions, risk factors, and multiple forms of disadvantage (Avila & Rose, 2019;Hayward & Williams, 2011). For instance, disengaged young people may be more susceptible to extreme poverty, social deprivation, a reliance upon school for meals, caregiving responsibilities for younger siblings, housing instability, psychological challenges, parental incarceration, poor social skills, low academic attainment, unsupportive teachers, and a disconnect between education and their needs (Nudzor, 2010;Rajasekaran & Reyes, 2019). Such adversity may manifest itself in three main ways: engagement, behavioural, and psychosocial challenges (Gutierrez-Garcia et al, 2018).…”
Section: Defining and Conceptualising 'Neet'mentioning
confidence: 99%
See 2 more Smart Citations